2015
DOI: 10.1364/oe.23.005485
|View full text |Cite
|
Sign up to set email alerts
|

101 kW superfluorescent source in all-fiberized MOPA configuration

Abstract: We present a high power all-fiberized master oscillator power amplifier (MOPA) structured superfluorescent source based on dual-cladding ytterbium-doped fiber. The seed source is a 0.814 W homemade amplified spontaneous emission (ASE) source. Two-stage high power fiber amplifier is utilized to boost the seed power to 1.01 kW with a beam quality of M(x)(2) = 1.688 and M(y)(2) = 1.728. The central wavelength of the output light is 1074.4 nm, and the full width at half maximum (FWHM) linewidth is about 8.1 nm. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…The ASE pump source plays a crucial role in generating temporally stable RDS mode locking. The ASE source from rare-earth-doped fiber has been proved to have good temporal stability [15], which is an ideal pump source for a Raman fiber laser [16]. It has been reported that high time domain stability could be obtained in a random distributed feedback Raman fiber laser under ASE source pumping [17].…”
mentioning
confidence: 99%
“…The ASE pump source plays a crucial role in generating temporally stable RDS mode locking. The ASE source from rare-earth-doped fiber has been proved to have good temporal stability [15], which is an ideal pump source for a Raman fiber laser [16]. It has been reported that high time domain stability could be obtained in a random distributed feedback Raman fiber laser under ASE source pumping [17].…”
mentioning
confidence: 99%
“…Xu et al [9] present a 1.01 kW, all-fiberized master oscillator power amplifier structured superfluorescent source based on dual-cladding ytterbium-doped fiber. The seed source was a 0.814 W homemade amplified spontaneous emission (ASE) source.…”
Section: Fiber Lasersmentioning
confidence: 99%
“…What is more, the presented high power SFSs in single-stage structure were often broadband and randomlypolarized [16][17][18][19] , while narrowband and polarization characteristics are required in practical applications [20,21] . Fortunately, employing master-oscillator-power-amplifier (MOPA) configuration can introduce a new horizon of high power SFS and leverage the high power SFS with special spectrum/polarization characteristics [22][23][24][25] and kilowatts operating power [26][27][28][29][30] . Besides, the output light of MOPAstructured SFS, in contrast to that of fiber MOPA seeded by standard resonant-cavity-based oscillator with self-pulsing effect, also has the advantages of high temporal stability [2,4] .…”
Section: Introductionmentioning
confidence: 99%